Preparation method of high-performance copper powder with high laser absorptivity and 3D printing method
By adding nano-ceramic particles to spherical copper powder and using acoustic resonance mixing technology to evenly adhere to the surface of the copper powder, the problem of low laser absorption rate of 3D printing copper powder is solved, the absorption rate is significantly improved, and high strength and high 3D printing using guided copper material.
Patent Information
- Application Number
- CN202411492287.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
AI Technical Summary
The laser absorption rate of existing 3D printed copper powder is low, making it difficult to achieve 3D printing and forming of high-performance copper materials, and the conductivity and thermal conductivity of pure copper materials are insufficient.
By adding nano -ceramic particles with higher laser absorption to the spherical copper powder, and using acoustic resonance hybrid technology, it is evenly attached to the surface of the copper powder. At the same time, the micro -amount auxiliary reagent is added to remove the oxide film on the surface of the copper powder to improve the moisturizing of nanoparticles. Wet.
Significantly improves the laser absorption rate of copper powder from 30% to 70%, allowing it to be successfully 3D printed through laser selective melting technology. It also improves the mechanical properties of pure copper and realizes 3D printing of high-strength and high-conductivity copper materials. .
Smart Images

Figure CN119328131A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powder material preparation, and relates to a preparation method of high-performance copper powder with high laser absorption rate and a 3D printing method. Background Art
[0002] As the raw material for 3D printing, metal powder must have properties such as good sphericity, good fluidity, and high laser absorption rate. The quality of powder plays a vital role in the performance of 3D printed parts.
[0003] Copper and copper alloys have excellent electrical conductivity, thermal conductivity, processing performance and corrosion resistance, and are widely used in power electronics, mechanical industry, aerospace and national defense and military industries. The copper and copper alloy materials produced by traditional preparation processes are subject to processing technology, cost and structural limitations, and are gradually unable to meet the ever-changing needs of modern processes. Research on high-efficiency, short-process and low-cost copper 3D printing technology is of great significance to promoting the continuous upgrading of the industry. However, the reflectivity of pure copper materials to lasers is very high. The laser absorption rate of pure copper powder with a particle size of 15-53μm is generally less than 30% at the commonly used 1064nm wavelength. 3D printed parts are prone to a large number of defects such as unfused and pores, which seriously affect the mechanical properties, electrical conductivity and thermal conductivity. Pure copper 3D printing is a difficult problem that needs to be overcome urgently. Although the laser absorption rate of copper alloys can be improved by adding alloying elements, alloying treatment is required in the smelting process, and then powder is made by means such as gas atomization. The introduction of alloying elements significantly reduces the electrical conductivity and thermal conductivity, which deteriorates the comprehensive performance of parts.
[0004] At present, pure copper is difficult to form through 3D printing due to its extremely low laser absorption rate, and 3D printed parts made of copper alloys have insufficient electrical and thermal conductivity. Therefore, it is of great significance to develop a preparation method and 3D printing technology for high-performance copper powder with high laser absorption rate. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a preparation method and a 3D printing method for high-performance copper powder with high laser absorption rate, so as to solve the problems that the laser absorption rate of the existing 3D printing copper powder is low and it is difficult to realize the 3D printing of high-performance copper materials. According to the characteristics of the laser 3D printing process, the preparation method adds nano-ceramic particles with higher laser absorption rate to the spherical copper powder, and makes the nano-ceramic particles evenly adhere to the surface of the spherical copper powder through acoustic resonance mixing, so as to effectively improve the laser absorption rate; a trace amount of auxiliary reagent is added to remove the oxide film on the surface of the copper powder and increase the wettability of the copper powder and nano-particles during the printing process, and the trace amount of auxiliary reagent can be completely volatilized during the printing process without any residue; at the same time, the nano-particles, as a reinforcing phase, can effectively improve the mechanical properties of pure copper, thereby realizing the direct preparation of high-strength and high-conductivity copper materials by 3D printing.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing high-performance copper powder with high laser absorption rate comprises the following steps:
[0008] Step 1: mixing spherical copper powder, nano-ceramic particles and auxiliary reagents to obtain mixed powder;
[0009] Step 2: placing the mixed powder obtained in step 1 into a grinding jar, and grinding and mixing the mixed powder evenly using an acoustic resonance mixer;
[0010] Step 3: Place the uniformly ground and mixed mixed powder in a vacuum drying oven for heat treatment. After the treatment, high-performance copper powder with high laser absorption rate can be obtained.
[0011] Specifically, auxiliary reagents can remove the oxide film on the copper surface during the 3D printing process, increase the wettability of copper and nanoparticles, and promote the uniform dispersion of nanoparticles. In addition, trace amounts of auxiliary reagents will evaporate rapidly during the high-energy-density laser 3D printing process and be blown to the filtration system through the wind field without leaving any impurities.
[0012] Furthermore, the particle size of the spherical copper powder is 15-53 μm or 45-105 μm.
[0013] Furthermore, the particle size of the nano-ceramic particles is 10-200 nm, and the type of the nano-ceramic particles is one or more combinations of chromium carbide, tungsten carbide, lanthanum hexaboride and molybdenum carbide.
[0014] Furthermore, the addition ratio of the nano ceramic particles is 0.5%-10% of the mass fraction of the spherical copper powder.
[0015] Furthermore, the auxiliary reagent is one or more combinations of KAlF4, stearic acid, KCl and NaF.
[0016] Furthermore, the addition ratio of the auxiliary agent is 0.05-1% of the mass fraction of the spherical copper powder.
[0017] Furthermore, when the mixed powder is uniformly ground and mixed by an acoustic resonance mixer in step 2, one or more combinations of pure copper, zirconium oxide and stainless steel grinding balls can be added as grinding balls, and the mass ratio of the grinding balls to the mixed powder is 0.5:1 to 2:1. The mixing acceleration of the acoustic resonance mixer is 40-80g, and the mixing time is 10-120min.
[0018] Furthermore, the heat treatment in step 3 is carried out under vacuum conditions at a temperature of 100-200° C., and is kept warm for 1-2 hours before being cooled in the furnace.
[0019] A 3D printing method, using the high-performance copper powder with high laser absorption rate prepared by the preparation method of the high-performance copper powder with high laser absorption rate as a raw material, specifically comprising the following steps:
[0020] Step 1: A three-dimensional model of a component part, and slicing the three-dimensional model;
[0021] Step 2: using the high-performance copper powder with high laser absorption rate as raw material, spreading the powder once on the substrate using a metal SLM printing device, and performing single-layer printing of the slices in sequence according to a certain scanning strategy;
[0022] Step 3: Repeat step 2 above until printing is completed to obtain the integrated and complete part.
[0023] Further, it also includes step 4;
[0024] Step 4: Take out the printed part together with the substrate, cut the part from the substrate using electric spark cutting, and perform grinding and polishing.
[0025] Furthermore, the certain scanning strategy is a strip scanning strategy or a chessboard scanning strategy.
[0026] Furthermore, the printing process of the slices is as follows: laser power 280-420W, scanning speed 300-800mm / s, scanning spacing 0.06-0.12mm, and powder layer thickness 30-60μm.
[0027] Furthermore, the substrate needs to be preheated before powder coating, and the preheating temperature of the substrate is 80-200°C.
[0028] The beneficial effects of the present invention are:
[0029] 1. The present invention uniformly attaches nano-ceramic particles with higher laser absorption rate to the surface of micron spherical copper powder through acoustic resonance mixing, which significantly improves the absorption rate of spherical copper powder under common 1064nm wavelength laser, and the absorption rate is increased from about 30% to about 70%, so that it can be smoothly formed by 3D printing through laser selective melting technology.
[0030] 2. The present invention can remove the oxide film on the copper surface during the printing process by adding a trace amount of auxiliary reagents to the spherical copper powder, increase the wettability of the nanoparticles, promote the uniform dispersion of the nanoparticles in the copper matrix, and remove them by laser evaporation during the printing process without residues and inclusions.
[0031] 3. The present invention adds nano-ceramic particles to a pure copper matrix (spherical copper powder) and forms it through laser selective melting technology, so that the nano-ceramic particles can be evenly dispersed in the copper matrix to form dispersion strengthening; at the same time, the extremely fast cooling speed of the laser selective melting technology can refine the grains and further improve the strength, thereby obtaining a high-strength and high-conductivity copper material (high-performance copper powder).
[0032] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0034] Figure 1 This is a microscopic morphology of pure copper powder and nano-ceramic particles attached to the surface of pure copper powder after being evenly mixed by acoustic resonance;
[0035] Figure 2 This is a comparison of the absorption rate of pure copper powder at different laser wavelengths before and after adding nano-ceramic particles. DETAILED DESCRIPTION
[0036] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0037] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0038] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0039] Example 1
[0040] A method for preparing high-performance copper powder with high laser absorptivity comprises the following steps:
[0041] Step 1: Take 970g of spherical copper powder with a particle size range of 15-53μm, 30g of chromium carbide ceramic particles with a particle size of 50-100nm and 5g of KAlF4 auxiliary reagent;
[0042] Step 2: Add 970 g of spherical copper powder, 30 g of chromium carbide ceramic particles and 5 g of KAlF4 into a grinding jar and mix using acoustic resonance at a mixing acceleration of 80 g and a mixing time of 25 min;
[0043] Step 3: Place the ground powder in a vacuum drying oven, heat at 120°C for 1 hour, cool it in the oven and take it out to obtain high-performance copper powder with high laser absorption rate.
[0044] like Figure 1 and Figure 2 As shown, the present invention uniformly attaches nano-ceramic particles with higher laser absorption rate to the surface of spherical micron copper powder through acoustic resonance mixing, which significantly improves the absorption rate of spherical copper powder under common 1064nm wavelength laser from about 30% to about 70%, so that it can be smoothly formed by 3D printing through laser selective melting technology.
[0045] In another embodiment, the particle size of the spherical copper powder may be 45-105 μm;
[0046] Example 2
[0047] A 3D printing method comprises the following steps:
[0048] Step 1: prepare a three-dimensional model of a component part, and slice the three-dimensional model. Use the high-performance copper powder with high laser absorption rate prepared by the method for preparing a high-performance copper powder with high laser absorption rate in Example 1 as a raw material, spread the powder once on the substrate using a metal SLM printing device, and perform single-layer printing of the slices in sequence according to the strip scanning strategy. The printing process is as follows: substrate preheating temperature 180°C, laser power 300W, scanning speed 350mm / s, scanning spacing 0.08mm, layer thickness 30μm;
[0049] Step 2: Repeat step 1 above until printing is completed to obtain a high-performance copper part;
[0050] Step 3: Take out the printed high-performance copper parts together with the substrate, cut them off from the substrate using electrospark cutting, and grind and polish them to obtain high-density high-performance copper parts.
[0051] Specifically, the metal SLM printing device has an SLM printing system, which includes a processor and a memory for storing executable instructions; the processor is configured to execute the executable instructions to perform the printing process described in step 1 in Example 2.
[0052] In another embodiment, the metal SLM printing device has a computer-readable storage medium on which a computer program is stored. When the computer program is executed by a processor, the printing process described in step 1 of embodiment 2 is implemented.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing high-performance copper powder with high laser absorptivity, characterized in that: The following steps are involved: Step 1: mixing spherical copper powder, nano-ceramic particles and auxiliary reagents to obtain mixed powder; Step 2: placing the mixed powder obtained in step 1 into a grinding jar, and grinding and mixing the mixed powder evenly using an acoustic resonance mixer; Step 3: Place the uniformly ground and mixed mixed powder in a vacuum drying oven for heat treatment. After the treatment, high-performance copper powder with high laser absorption rate can be obtained.
2. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: The particle size of the spherical copper powder is 15-53 μm or 45-105 μm.
3. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: The particle size of the nano-ceramic particles is 10-200 nm, and the types of the nano-ceramic particles are one or more combinations of chromium carbide, tungsten carbide, lanthanum hexaboride and molybdenum carbide.
4. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: The addition ratio of the nano ceramic particles is 0.5%-10% of the mass fraction of the spherical copper powder.
5. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: The auxiliary reagent is one or more combinations of KAlF4, stearic acid, KCl and NaF.
6. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: The addition ratio of the auxiliary agent is 0.05-1% of the mass fraction of the spherical copper powder.
7. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: When the mixed powder is uniformly ground and mixed by an acoustic resonance mixer in step 2, one or more combinations of pure copper, zirconium oxide and stainless steel grinding balls can be added as grinding balls, the mass ratio of the grinding balls to the mixed powder is 0.5:1 to 2:1, the mixing acceleration of the acoustic resonance mixer is 40-80g, and the mixing time is 10-120min.
8. The method for preparing high-performance copper powder with high laser absorption rate according to claim 1, characterized in that: The heat treatment in step 3 is carried out under vacuum conditions at a temperature of 100-200° C., and is kept at this temperature for 1-2 hours before being cooled in the furnace.
9. A 3D printing method, characterized in that: The high-performance copper powder with high laser absorption rate prepared by the method for preparing the high-performance copper powder with high laser absorption rate according to any one of claims 1 to 8 is used as a raw material, and specifically comprises the following steps: Step 1: A three-dimensional model of a component part, and slicing the three-dimensional model; Step 2: using the high-performance copper powder with high laser absorption rate as raw material, spreading the powder once on the substrate using a metal SLM printing device, and performing single-layer printing of the slices in sequence according to a certain scanning strategy; Step 3: Repeat step 2 above until printing is completed to obtain the integrated and complete part.
10. The 3D printing method with high laser absorption rate according to claim 9, characterized in that: Also includes step 4; Step 4: Take out the printed part together with the substrate, cut the part from the substrate using electric spark cutting, and grind and polish it.
11. The 3D printing method with high laser absorption rate according to claim 9, characterized in that: The certain scanning strategy is a strip scanning strategy or a chessboard scanning strategy.
12. The 3D printing method with high laser absorption rate according to claim 11, characterized in that: The printing process of the slices is as follows: laser power 280-420W, scanning speed 300-800mm / s, scanning spacing 0.06-0.12mm, and powder layer thickness 30-60μm.
13. The 3D printing method with high laser absorption rate according to claim 12, characterized in that: The substrate needs to be preheated before powder coating, and the preheating temperature of the substrate is 80-200°C.
Citation Information
Cited By
Preparation method of micron LaB6 copper-based composite material, material and laser additive manufacturing method of micron LaB6 copper-based composite material
CN121406934A